MAKNA SIMBOL DAN KATA DALAM NOVEL HATI SINDEN KARYA DWI RAHYUNINGSIH: KAJIAN HERMENEUTIKA PAUL RICOEUR - Sri Wulandari (EDU-KATA, 2018)
These studies generally describe Paul Ricoeur hermeneutics in the novel Heart Sinden Dwi works Rahyuningsih, while specifically aimed to describe the meaning of the symbols and words in the novel Heart Sinden Rahyuningsih Dwi works. The research data was sourced from the novel Heart Sinden Rahyuningsih Dwi works. Data collected by technical read, see, and record. The results showed that the words of the novel Heart Sinden contains many symbols. The symbols which include sinden heart symbol, symbols Sayem name, symbol Gusti words, and symbols of the Java language expression. Based on the results of the study concluded that the novel Heart Sinden float images of Javanese culture and many reveal the attitude of Javanese life which includes attitudes Rila, Nrima, and patient which is reflected by the attitude and behavior of the characters in the story.